Estudio comparativo de costos y rendimiento: metodología tradicional vs steel framing en una vivienda unifamiliar del sector Mucho Lote - Gadvay Caiza, Josselyn Estefanía (2024)
The present degree project, developed at the Universidad Laica Vicente Rocafuerte de Guayaquil (ULVR), focuses on the cost and performance comparison between two construction systems in the construction of single-family homes in the Mucho Lote sector: the traditional system and the Steel Framing system. The general objective of the study is to evaluate and compare both systems in terms of costs, execution time, and efficiency, to determine which of them offers better results in the specific context of this urban sector. To achieve this objective, a quantitative-comparative methodology was employed, which consisted of the analysis of unit prices, detailed budgets, and the estimation of the time required for construction with both methods. The results obtained show that the Steel Framing system is approximately 5.60% more economical than the traditional system in terms of direct costs, and also allows for a reduction in the total construction time by 31%, going from 27 to 20 days. This reduction in execution time is significant, especially in projects with time constraints. The main conclusion of the study is that Steel Framing not only reduces costs and construction time but also minimizes material waste and improves the energy efficiency of the homes, making it a viable, sustainable, and competitive option for construction projects in urban environments.